Financial Management Practices in Small and Medium Sized Enterprises: Empirical Evidence from the District of Ampara in Sri Lanka - Rauf, Ahamed Lebbe Abdul (International Journal of Economics, Business and Management Studies, 2016)
This research examines a study of financial management practices (FMP) in small and medium sized enterprises. The objectives are to evaluate the impact of working capital management, financial planning and control and total quality management system on financial management practices in the SME. The primary data are collected through standardized questionnaires from sixty owners of the SMEs in Ampara district of Sri Lanka. The collected data were analyzed by descriptive, correlation and regression analysis. With respect to the regression results, value for R square (0.513) indicates that working capital management, financial planning and control and total quality management system presents 51.3 percent of total variation of the dependent variable. Further results of this study indicate that working capital management and total quality management indicator positive significant relationship from regression tools while financial planning and control have a negative no significant relationship on financial management practices. This study suggests that government policies should be more effective and to provide the training programs for the owners and employees of SMEs. And also to eliminate the cash management difficulties, use effective inventory techniques, maintain the customers’ creditworthiness and prepare the monthly review of actual achievements for the success of small medium sized enterprises in Sri Lanka.